Alkaline Phosphatase Activity Is a Key Determinant of Vascular Responsiveness to Norepinephrine. Issue 4 (October 2020) - Jackson, Edwin K.; Cheng, Dongmei; Ritov, Vladimir B.; Mi, Zaichuan
Abstract : Here, we tested the hypothesis that TNAP (tissue nonspecific alkaline phosphatase) modulates vascular responsiveness to norepinephrine. In the isolated, Tyrode's-perfused rat mesentery, 50 µmol/L of L-p-bromotetramisole (L-p-BT; selective TNAP inhibitor, Ki =56 µmol/L) significantly reduced TNAP activity and caused a significant 9.0-fold rightward-shift in the norepinephrine concentration versus vasoconstriction relationship. At 100 µmol/L, L-p-BT further reduced mesenteric TNAP activity and caused an additional significant right-shift of the norepinephrine concentration versus vasoconstriction relationship. A higher concentration (200 µmol/L) of L-p-BT had no further effect on either mesenteric TNAP activity or norepinephrine-induced vasoconstriction. L-p-BT did not alter vascular responses to vasopressin, thus ruling-out nonspecific suppression of vascular reactivity. Since in the rat mesenteric vasculature α1 -adrenoceptors mediate norepinephrine-induced vasoconstriction, these finding indicate that TNAP inhibition selectively interferes with α1 -adrenoceptor signaling. Additional experiments showed that the effects of TNAP inhibition on norepinephrine-induced vasoconstriction were not mediated by accumulation of pyrophosphate or ATP (TNAP substrates) nor by reduced adenosine levels (TNAP product). TNAP inhibition significantly reduced the Hillslope of the norepinephrine concentration versus vasoconstriction relationship from 1.8±0.2 (consistent with positive cooperativity of α1 -adrenoceptor signaling) to 1.0±0.1 (no cooperativity). Selective activation of A1 -adenosine receptors, which are known to participate in coincident signaling with α1 -adrenoceptors, reversed the suppressive effects of L-p-BT on norepinephrine-induced vasoconstriction. In vivo, L-p-BT administration achieved plasma levels of ≈60 µmol/L and inhibited mesenteric vascular responses to exogenous norepinephrine and sympathetic nerve stimulation. TNAP modulates vascular responses to norepinephrine likely by affecting positive cooperativity of α1 -adrenoceptor signaling via a mechanism involving A1 receptor signaling. Abstract : Supplemental Digital Content is available in the text.